Pengaruh Penambahan Sari Daun Biduri (Calotropis gigantea) Terhadap Karakteristik Fisikokimia Keju Lunak - Thadeus Octovianus Welin; Sulmiyati Sulmiyati; Pieter Rihi Kale; Gemini Ermiani Mercurina Malelak (Jurnal Ilmu dan Industri Peternakan, 2023)
Cheese is a food product with milk-based ingredients, but the processing it requires high production costs due to the big cost of the rennet enzyme as a coaugulant, so it necessary to find an alternative to the rennet enzyme, namely the protease enzyme from the biduri plant. The purpose of this study was to determine the effect of adding biduri leaf juice on the physicochemical characteristics of soft cheese. This research method, which uses a Completely Randomized Design (CRD) with 3 preparations and 5 replications. The additions of biduri leaf juice with different levels of 1,5%; 2% and 2,5%(v/v). The result showed that the curd production was around 19,50-29,56%, the resulting whey release was 62,40-66,70, the pH value was 6.62-6,82, the lactic acid content was 0,43-0,67 and color value of soft cheese 2,50 (green)-4,70 (white), aroma value 3,00 (slightly cheese flavored)-3,30 (slightly cheese flavored), taste value 4,30 (moderately bitter)-5,00 (not bitter), texture value 3,50 (quit denset)-4,50 (slightly mushy) and level of preference 2,70 (somewhat like)-3,80 (like). The addition of biduri leaf juice as much 2% in cheese processing gives the best cheese yield and the result is formation of curd 24,03%; whey release 66,10; pH 6,76; lactic acid content 0,52%. The result of the assessment of soft cheese with addition of 2% biduri leaf juice had a color value of 3,00 (slightly green), an aroma value of 3,00 (slightly cheese flavored), a taste value of 5,00 (not bitter), a texture value of 4,20 (quite dense) and preference level of 3,70 (like).